Storyworlds across media toward a media-conscious narratology - Ryan, Marie-Laure 1946-; Thon, Jan-Noël (Frontiers of narrative, 2014)
The proliferation of media and their ever-increasing role in our daily life has produced a strong sense that understanding media--everything from oral storytelling, literary narrative, newspapers, and comics to radio, film, TV, and video games--is key to understanding the dynamics of culture and society. Storyworlds across Media explores how media, old and new, give birth to various types of storyworlds and provide different ways of experiencing them, inviting readers to join an ongoing theoretical conversation focused on the question: how can narratology achieve media-consciousness? The first part of the volume critically assesses the cross- and transmedial validity of narratological concepts such as storyworld, narrator, representation of subjectivity, and fictionality. The second part deals with issues of multimodality and intermediality across media. The third part explores the relation between media convergence and transmedial storyworlds, examining emergent forms of storytelling based on multiple media platforms. Taken together, these essays build the foundation for a media-conscious narratology that acknowledges both similarities and differences in the ways media narrate.